CHARACTERIZATION OF UTERINE NK CELLS IN WOMEN WITH INFERTILITY OR RECURRENT PREGNANCY LOSS AND ASSOCIATED ENDOMETRIOSIS - Giuliani, Emma (2014)
PROBLEM: Uterine natural killer cells (uNK) have been thought to play a key role in endometriosis and infertility. We investigated the expression of CD56, CD16 and NKp46 in endometrial tissues from 61 women with unexplained recurrent pregnancy loss (uRPL) or infertility (UI), and correlated this with the presence or absence of endometriosis. The results from the patients with sub-fertility were compared to those from 10 fertile patients. METHOD OF STUDY: Mid-secretory phase endometrial biopsies were obtained and the endometrial expression of CD56, CD16 or NKp46 was identified by immunohistochemistry and quantified (ImageJ Software). RESULTS: The percentage of CD16(+) cells was higher in women with uRPL (7.9±3.2) and UI (9.0±5.5), even when these conditions were associated with endometriosis (8.9±5.3), compared to fertile patients (5.6±2.4, p<0.05). Likewise, the ratio of NKp46(+):CD56(+) cells was higher in women with uRPL (0.28±0.25) and UI (0.21±0.2), even when these conditions were associated with endometriosis (0.19±0.14), compared to fertile patients (0.1±0.1, p<0.05). No differences were observed when comparing CD56. CONCLUSIONS: Women, with or without endometriosis, who have larger populations of cytotoxic CD16(+) uNK cells and/or higher populations of NKp46(+)CD56(+) cells may be at greater risk for infertility disorders resulting from an inflammtory environment occuring during implantation or later during decidualization.